Penyuluhan Pentingnya Vaksin HPV untuk Mencegah Kanker Serviks Sedini mungkin di Kabupaten Takalar - Sumarmi Sumarmi; Salmah Arafah; Ernawati Ernawati; Kamriana Kamriana; Mantasia Mantasia; Riska Nuryana; Alwi Alwi; Sri Kurnia Sah Puteri; Dewi Dewi (Compromise Journal Community Proffesional Service Journal, 2024)
Cervical cancer is one of the most common types of cancer in the female genital organs caused by human papillomavirus (HPV), and preventive measures are highly recommended rather than curative measures. Prevention efforts are still poorly understood, so education is needed to increase vaccination coverage. The aim of this service is to increase participants' understanding of cancer vaccines. This method was used to discuss with partners at SDN Pusat No. 1 Patalasang District. Takalar, and students and teachers participate. Participants' knowledge was assessed through pre-test and post-test. The test result in front of 6 teachers and 15 students was 71.4, increasing to 98.2 at the time of the test. All service participants were satisfied with the implementation of the service because they felt the information was very useful and they needed it. All participants feel the benefits of using the services. Participants hope to continue this service in the future with free pap smears and vaccinations. It can be concluded that advice on cancer prevention and vaccination increased participants' understanding from 71.4 to 98.2 and was highly appreciated by the participants.